2023
DOI: 10.1038/s41467-023-43463-0
|View full text |Cite
|
Sign up to set email alerts
|

Middle east warming in spring enhances summer rainfall over Pakistan

Baosheng Li,
Lei Zhou,
Jianhuang Qin
et al.

Abstract: The edge of a monsoon region is usually highly sensitive to climate change. Pakistan, which is located on the northern edge of the Indian monsoon, is highly vulnerable to heavy rainfall and has witnessed several debilitating floods exacerbated by global warming in recent years. However, the mechanisms for the frequent Pakistan floods are yet not fully understood. Here, we show that the Middle East is undergoing an increase in land heating during spring, which is responsible for 46% of the intensified rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A northward shift of the Somali Jet in response to the enhanced meridional temperature gradient between the Middle East and the southern Arabian Sea owing to a stronger surface heating (and resulting lower surface pressures) over the Middle East is also seen in spring, as highlighted in 128 . In the MENA region in particular, the air temperature has been increasing at a rate of about 0.04 K year −1 and the sea-level pressure has been dropping at about 0.016 hPa year −1 (Table 3 ), trends that are steeper than those seen elsewhere (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…A northward shift of the Somali Jet in response to the enhanced meridional temperature gradient between the Middle East and the southern Arabian Sea owing to a stronger surface heating (and resulting lower surface pressures) over the Middle East is also seen in spring, as highlighted in 128 . In the MENA region in particular, the air temperature has been increasing at a rate of about 0.04 K year −1 and the sea-level pressure has been dropping at about 0.016 hPa year −1 (Table 3 ), trends that are steeper than those seen elsewhere (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, the significant difference in temperatures (> 2°C) between the two regimes is also evident over the Eastern Mediterranean and the Middle East (EMME) which is a prominent climate change hotspot 45 . The warming over these dry and desert regions are proposed to have enhanced the summer rainfall over Pakistan 46 . However, our focus is only over the Indian region in this study.…”
Section: Figure 1 Regime Shift During the Pre-monsoon Season (Mar-apr...mentioning
confidence: 99%
“…Strong evidence indicates a growing trend in extreme precipitation in South Asia (Seneviratne et al 2021), along with an increase in the intensity and westward movement of the monsoon over Pakistan (Hanif et al 2013). The latest research suggests that warming land surface temperature in the Middle East region during spring contributes to summer precipitation in monsoon edge regions, such as Pakistan (Li et al 2023). Recent studies have shown that monsoon precipitation in Pakistan exhibits high spatial and temporal variability (Gadiwala andBurke 2013, Hanif et al 2013).…”
Section: Introductionmentioning
confidence: 99%